Melatonin protects ADSCs from ROS and enhances their therapeutic potency in a rat model of myocardial infarction. Issue 9 (17th June 2015) - Zhu, Ping; Liu, Jianfeng; Shi, Jinxin; Zhou, Qian; Liu, Jie; Zhang, Xianwei; Du, Zhiyan; Liu, Qiaowei; Guo, Yuanyuan
Abstract Myocardial infarction (MI) is a major cause of death and disability worldwide. In the last decade, mesenchymal stem cells (MSCs) based cell therapy has emerged as a promising therapeutic strategy. Although great advance have been made using MSCs to treat MI, the low viability of transplanted MSCs severely limits the efficiency of MSCs therapy. Here, we show evidence that ex vivo pre‐treatment with melatonin, an endogenous hormone with newly found anti‐oxidative activity, could improve survival and function of adipose tissue derived MSCs (ADSCs) in vitro as well as in vivo. ADSCs with 5 μM melatonin pre‐treatment for 24 hrs showed increased expression of the antioxidant enzyme catalase and Cu/Zn superoxide dismutase (SOD‐1), as well as pro‐angiogenic and mitogenic factors like insulin‐like growth factor 1, basic fibroblast growth factor, hepatocyte growth factor (HGF), epidermal growth factor. Furthermore, melatonin pre‐treatment protected MSCs from reactive oxygen species (ROS) induced apoptosis both directly by promoting anti‐apoptosis kinases like p‐Akt as well as blocking caspase cascade, and indirectly by restoring the ROS impaired cell adhesion. Using a rat model of MI, we found that melatonin pre‐treatment enhanced the viability of engrafted ADSCs, and promoted their therapeutic potency. Hopefully, our results may shed light on the design of more effective therapeutic strategies treating MI by MSCs in clinic.